Central America : structural foundations for regional financial integration - Brenner, Patricia DeCoster (International Monetary Fund, 2006)
Intraregional financial activity in Central America has grown substantially in the last decade, contributing to efficiency and economic development. At the same time, the expansion of activities by regional conglomerates has lead to increased challenges to supervisory authorities in containing the risks of contagion. Prepared as part of the Central America Financial Sector Regional Project by an IMF and World Bank staff team, this book outlines trends in the region's financial sector integration and supervisory responses, and development of the insurance sector, payment and securities settlement arrangements, and worker remittances. It addresses the many common policy challenges facing Central American countries--Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, and Panama--in financial sector reform. The book makes key policy recommendations that could prove to be invaluable for the various contributors who are providing financial and technical support for financial sector reforms in Central America. --Publisher's description.